2005
DOI: 10.1051/agro:2005044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green manuring on the yield of sweet corn

Abstract: Experiments were conducted on a clay soil to assess the effects of green manuring of three annual legumes and nitrogen fertilization on sweet corn (Zea mays var. saccharata Sturt.), during three growing seasons (2001-2003). The green manuring legumes were field pea (Pisum sativum L.), common vetch (Vicia sativa L.) and faba bean (Vicia faba L.) N fertilization ranged from 0 to 360 kg ha-1. On a three-year average, field pea (3 065 kg ha-1) and common vetch (2 647 kg ha-1) consistently had higher aboveground dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
3
11
1
2
Order By: Relevance
“…The lower N production in winter wheat treatment was expected because winter wheat does not fix N and because the grain, which contains a high level of N, was removed. These findings are similar to results obtained by Plotkin (2000), Turgut et al (2005), and Mitchell and Teel (1977) who found that 90% of N accumulation in legume cover crops was in the haulm.…”
Section: Cover Cropssupporting
confidence: 92%
See 2 more Smart Citations
“…The lower N production in winter wheat treatment was expected because winter wheat does not fix N and because the grain, which contains a high level of N, was removed. These findings are similar to results obtained by Plotkin (2000), Turgut et al (2005), and Mitchell and Teel (1977) who found that 90% of N accumulation in legume cover crops was in the haulm.…”
Section: Cover Cropssupporting
confidence: 92%
“…Harvested cover crop biomass was redistributed in the harvested area. N concentration was measured by the Micro-Kjeldahl Technique (Turgut et al 2005) on both above-ground and root samples.…”
Section: Cover Crop Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There was increased growth and production of tomatoes under cultivation of hairy vetch Vicia villosa, demonstrating the efficiency of N supply by green manure , Tosti et al, 2012 and increased yields of sweet corn with field pea and common vetch (Turgut et al, 2005). Green manure improves the physical, chemical and biological properties of soil (Sharifi et al, 2014) including water retention, cation exchange capacity and microbial activity (Riutta et al, 2012;Dash et al, 2014).…”
Section: Total and Commercial Productivity Of Potatomentioning
confidence: 98%
“…Leguminous plants as green manure represent an alternative to mineral fertilizers, as they fix, accumulate and provide large quantities of nitrogen to crops , Turgut et al, 2005. This may reduce or replace conventional chemical fertilizers in production systems, especially by releasing N in organic production systems (Ferreira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%